Application-Based CRM Relationship Implementation for Micro, Small and Medium Enterprises - B S Kusuma; I F Ramdhani; Z Azhara (Universitas Komputer Indonesia, 2022)
This study aims to maintain good relations with consumers so that consumers do not turn to other competitors. The method used is the prototype method, which uses an approach to create a program quickly, gradually, making the information system better and easier. By using Customer Relationship Management (CRM) it can be useful for sales so that they can have good relations with consumers and so that consumers do not turn to others.